2020
DOI: 10.1111/pbi.13424
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation, evolution and utilization of natural alleles for cold adaptability at the reproductive stage in rice

Abstract: Genetic studies on cold tolerance at the reproductive stage in rice could lead to significant reductions in yield losses. However, knowledge about the genetic basis and adaptive differentiation, as well as the evolution and utilization of the underlying natural alleles, remains limited. Here, 580 rice accessions in two association panels were used to perform genome-wide association study, and 156 loci associated with cold tolerance at the reproductive stage were identified. Os01g0923600 and Os01g0923800 were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 56 publications
2
32
0
Order By: Relevance
“…Exploring and utilizing favourable alleles is an effective method for improving crop traits (Guo et al ., 2020). Substantial allelic variation was identified in ramie germplasms with respect to the fibre yield‐associated candidate genes identified in the current study, and different haplotypes showed considerable differences in fibre yield (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Exploring and utilizing favourable alleles is an effective method for improving crop traits (Guo et al ., 2020). Substantial allelic variation was identified in ramie germplasms with respect to the fibre yield‐associated candidate genes identified in the current study, and different haplotypes showed considerable differences in fibre yield (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work on the population dynamics of M. musculus from Myanmar showed evident population expansion in the Cytb sequence data that began about 5400 (95% CI: 2300-8000) years ago (Maung Maung Theint et al, 2020). In addition, the migration from southern China to the Japanese archipelago was deduced to have occurred 3500 years ago (Li et al, 2020b), which may be correlated with the introduction of cold-tolerant temperate japonica rice strains developed in response to the extreme environmental degradation 4200 years ago (Mao et al, 2019;Guo et al, 2020;Gutaker et al, 2020).…”
Section: Inference Of the Evolutionary History Of The House Mouse From Whole Mitochondrial Genome Sequencesmentioning
confidence: 99%
“…At the flowering stage, ambient temperature equal to or lower than 20°C lasting for 3 days would seriously affect the seed setting rate for rice (Shinada et al., 2013). Previous studies on the impacts of chilling on rice production were based on field experiments with cold water irrigation (Han & Koh, 2000; Matsumura et al., 2012), natural chilling treatment (Guo et al., 2020) and an artificial climate chamber (Farrell et al., 2006). Such studies have two common limitations: (a) they only focussed on the low temperature or the duration of the low temperature but not the two factors together; (b) the diurnal temperature range was not taken into consideration because the treatment temperature was fixed during the daytime or night‐time.…”
Section: Introductionmentioning
confidence: 99%